PENGARUH PERMAINAN TRADISIONAL LOMPAT TALI DAN ENGKLEK TERHADAP PERKEMBANGAN MOTORIK KASAR ANAK USIA 5–6 TAHUN - Kurnia Taufik; M. Alwi Hidayat; Intan Kusumawardani (Journal Sport Science, Health and Tourism of Mandalika (Jontak) e-ISSN 2722-3116, 2025)
Traditional games are recognized not only for their cultural and recreational value but also for their potential to stimulate physical and cognitive development in early childhood. This study aims to analyze the effect of two Indonesian traditional games, jump rope and hopscotch, on the gross motor development of children aged 5–6 years. The research used a quasi-experimental design with a pretest–posttest two-group model involving 20 children from RA Ittihadul Khairi, divided equally into jump rope and hopscotch groups. The intervention lasted four weeks, conducted three times per week for 20 minutes per session. The data were collected using a validated observation sheet referring to the indicators of balance, coordination, agility, strength, and movement accuracy from the Early Childhood Development Standards (Permendikbud No.137/2014). The reliability test using Cronbach’s Alpha showed a high level of consistency (α = 0.87). Data were analyzed using paired and independent sample t-tests after testing normality and homogeneity. The results revealed that both games significantly improved children’s gross motor skills (p < 0.05), with no significant difference between groups (p = 0.818). In conclusion, jump rope and hopscotch are equally effective in enhancing gross motor development in early childhood and are recommended as culturally relevant physical activities in PAUD programs.